Développer puis réduire les expressions suivantes :
1) ( x + 1 )² + (2x+1)²
2) ( x - 1 )² - ( x+2)²
3) (2a + 1 ) ( 2a- 1 )

1
(x²+2x+1) + (4x² +4x+1)
= 5x²+6x+2
1)x2+2x+1+4x2+4x+1=5x2+6x+2 2) x2-2x+1-x2+4x+4=2x+5 3) 4a2-2a+2a-1= 4a2-1

Réponses

Meilleure réponse !
2014-01-07T13:33:08+01:00
Bonjour,

1) (x + 1 )² + (2x + 1)² = (x² + 2x + 1) + (4x² + 4x + 1)
                                      = x² + 2x + 1 + 4x² + 4x + 1
                                      = 5x² + 6x + 2

2) (x - 1 )² - (x + 2)² = (x² - 2x + 1) - (x² + 4x + 4)
                                = x² - 2x + 1 - x² - 4x - 4
                                = -6x - 3

3) (2a + 1)(2a- 1) = (2a)² - 1²    [en appliquant la formule (A+B)(A-B° = A² - B² ]
                               = 4a² - 1